DEVELOPMENT OF MICE AND HAMSTER EMBRYOS IN KSOMAA AND HECM-6 MEDIUM - Rosadi, Bayu; Agus Setiadi, M; Sajuthi, Dondin; Boediono, Arief (Jurnal Veteriner, 2008)
The purpose of the present study was to investigate the viability of mice and hamster embryos developed in Kalium Simplex Optimized Medium amino acid (KSOMaa) and Hamster Embryo Culture Medium-6 (HECM-6) medium. Female DDY mice were superovulated by injection i.p. of 5 IU Pregnant Mare Serum Gonadotropine (PMSG) and 5 IU Human Chorionic Gonadotropine (hCG) in 48 h interval, hamster (Phodopus campbelli) injected by 2.5 IU PMSG and 2.5 IU hCG 48 h later. Then females were mated with fertile males. Eight-cell embryos were recovered at day 3 after natural mating. The mice embryos were cultured in KSOMaa+5% NBCS (New Born Calf Serum) (T1) and HECM-6+5% NBCS (T2), the hamster embryos were cultured in KSOMaa+5% NBCS (T3) and HECM-6 + 5% NBCS (T4) for further development at 37oC in a humidified atmosphere of 5% CO2 in air for 48 h. The examinations were replicated five times. The T1 embryos developed to compact morulla and early blastocyst 100% (140/140), 92.1% (129/140) to blastocyst and expanded blastocyst, and 22.9% (32/140) became hatching/hatched. The T3 reached 100% (60/60) to compact morulla and early blastocyst, 85.0% (51/60) blastocyst, and 48.3% (29/60) expanded blastocyst, no embryo observed hatching/hatced. The T2 embryos had more expanded blastocyst than T3 (P<0.05), hatching/hatched rate higher than T1 and T3 but lower than T4 (P<0.05). Shortly, KSOMaa enable to support 8-cell stage mice and hamster embryo, but the hamster embryo developed lower at expanded blastocyst stage. HECM-6 is more appropriate than KSOMaa to support 8-cell mice embryos development and suitable to develop 8-cell stage hamster embryos.
Keywords: embryo, medium, mice, hamster